Study to determine the optimum parameter of the electro discharge machine die sinked 4 litres bottle neck - Bangit, Grunsin (2008)
Bottle mould making technology has become one of the most important industries nowadays. However, the bottle necks mould making process is given less attention and special for the quality surface finish of the bottle neck mould. In manufacturing industry, surface quality of the mould is very important because surface quality is the main factor to determine the quality of the product. The objectives of this research are to investigate the optimum EDM Die Sinked parameters on bottle neck mould surface. The specimen material used in this research is stavax and copper as an electrode material. The machining parameters consider in this research are discharge current, gap voltage and pulse-on time. Surface finish in this experiment is measured with Marh Perthometer and full factorial design method is apply as a design of experiment to determine the optimum parameter of the EDM Die Sinked on bottle neck mould. The results shows that after machining with EDM Die Sinked, the better values of surface roughness got was 0.593 p.m but that's not the optimum result because at the same time we cannot got the actual dimension same as 4 liters bottle neck elctrode dimension that we used. So, the optimum parameter of EDM Die Sinked in this reseach was when we got values of surface roughness equal to 3.825 gin. As a conclusion, the electrode of 4 liters bottle neck was successfully tested by using EDM Die Sinked and the optimum parameter had been archieved.